2007
DOI: 10.1038/sj.onc.1210314
|View full text |Cite
|
Sign up to set email alerts
|

Human INT6 interacts with MCM7 and regulates its stability during S phase of the cell cycle

Abstract: The mouse int6 gene is a frequent integration site of the mouse mammary tumor virus and INT6 silencing by RNA interference in HeLa cells causes an increased number of cells in the G2/M phases of the cell cycle, along with mitotic defects. In this report, we investigated the functional significance of the interaction between INT6 and MCM7, which was observed in a two-hybrid screen performed with INT6 as bait. It was found that proteasome inhibition strengthens interaction between both proteins and that INT6 sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Protein profiles generated by 2D liquid chromatographic separation of whole cell lysates similarly showed no significant changes on eIF3e knockdown (data not shown) and there was only a minor increase in the level of total protein ubiquitinylation ( Figure 2c). Ubiquitination of MCM7 was slightly increased on eIF3e knockdown, whereas total MCM7 level was slightly decreased (Supplementary Figure 1), as reported previously (Buchsbaum et al, 2007). These data indicate that eIF3e does not influence global protein levels in human cells and suggest instead its possible involvement in the regulation of a specific subset of proteins.…”
Section: Elevated Eif3e Protein Levels In Human Breast Cancersupporting
confidence: 87%
See 1 more Smart Citation
“…Protein profiles generated by 2D liquid chromatographic separation of whole cell lysates similarly showed no significant changes on eIF3e knockdown (data not shown) and there was only a minor increase in the level of total protein ubiquitinylation ( Figure 2c). Ubiquitination of MCM7 was slightly increased on eIF3e knockdown, whereas total MCM7 level was slightly decreased (Supplementary Figure 1), as reported previously (Buchsbaum et al, 2007). These data indicate that eIF3e does not influence global protein levels in human cells and suggest instead its possible involvement in the regulation of a specific subset of proteins.…”
Section: Elevated Eif3e Protein Levels In Human Breast Cancersupporting
confidence: 87%
“…In Drosophila eIF3e was shown to be a positive regulator of cullin neddylation, thus regulating degradation through the ubiquitin-proteasome pathway of substrates of cullin-containing ubiquitin ligases (RencusLazar et al, 2008). Other studies reported specific interaction of eIF3e with HIF-2a (Chen et al, 2007) or with MCM7 (Buchsbaum et al, 2007), leading to proteasomal degradation or stabilization of the eIF3e partner protein, respectively. In our experiments, eIF3e knockdown induced a slight accumulation of polyubiquitinylated proteins (Figure 2c), including MCM7 (Supplementary Figure 1), leaving open the possibility that some of the biological consequences observed might reflect an involvement of eIF3e in ubiquitin-dependent proteolysis.…”
Section: Discussionmentioning
confidence: 98%
“…This screen led to the identification of several INT6 interactors such as RFP, MCM7, and several subunits of the eIF3 complex, of the CSN, and of the 19S proteasome regulatory particle as previously reported (Morris-Desbois et al 1999;Hoareau Alves et al 2002;Buchsbaum et al 2007). Among the clones obtained in this screen, three encoded MIF4GD.…”
Section: Interaction Between Int6 and Mif4gdmentioning
confidence: 90%
“…In particular, it has been reported that INT6 is partly located in the nucleus (Desbois et al 1996;MorrisDesbois et al 1999;Buchsbaum et al 2007;Grzmil et al 2010), and Watkins and Norbury (2004) have shown that in nontransformed cells this localization was reduced in S phase. In agreement with a dual location in the nucleus and the cytoplasm, the protein has an N-terminal nuclear export sequence and an internal nuclear localization signal, indicating that it is likely to shuttle between both compartments (Guo and Sen 2000).…”
Section: Relationship Between Histone Mrna Translation and Other Rolementioning
confidence: 99%
See 1 more Smart Citation